Serum‐free complete medium, an alternative medium to mimic androgen deprivation in human prostate cancer cell line models. Issue 3 (1st December 2017) - Fiandalo, Michael V.; Wilton, John H.; Mantione, Krystin M.; Wrzosek, Carol; Attwood, Kristopher M.; Wu, Yue; Mohler, James L.
Abstract : Background: Almost all men who present with advanced prostate cancer (CaP) and some men who fail therapy for clinically localized CaP are treated with androgen deprivation therapy (ADT). CaP cell lines are used to identify and characterize new agents for ADT or investigate mechanisms of ADT resistance. CaP cell lines are maintained in culture medium that contains fetal bovine serum, which contains testosterone (T). Androgen deprivation experiments are performed using media supplemented with androgen‐free serum, such as charcoal stripped fetal bovine serum (CS‐FBS). However, CS‐FBS composition varies from batch‐to‐batch and variations may impact experimental reproducibility. Serum free media (SFM) may provide a better defined alternative to media supplemented with CS‐FBS (CSM). Methods: Cell growth of six human CaP cell lines was assessed using 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT). Androgen levels were measured using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). Results: MTT assays showed 5 of 6 CaP cell lines grew after 6 days of culture in androgen‐ deprived SFM or CSM. LNCaP and VCaP growth was stimulated when cells were cultured in SFM or CSM supplemented with T. LNCaP, C4‐2, LAPC‐4, and VCaP cell growth was inhibited when cultured in SFM or CSM with T and bicalutamide. LC‐MS/MS data showed LAPC‐4 cells produced similar DHT levels when cultured in T‐supplemented SFM or CSM. Dutasteride impaired T to DHT metabolism in LAPC‐4. Conclusions: Media composition contributed to growth differences observed between CaP cells cultured in SFM or CSM. However, the differences in media composition did not impair CaP cell response to T‐stimulated growth, bicalutamide growth inhibition, metabolism of T, or dutasteride efficiency. SFM can be used as a better defined alternative to CSM for androgen deprivation experiments.